Han van Meegeren revisited. His art & list of works - Kreuger, Frederik H. ([Quantes], 2010)
After completing his biography of Han van Meegeren, both in Dutch and in English, the author continued to collect information about the artist's life and his art. Although the amount and the importance of the information was not sufficient to justify a new and extended biography, he did not want the data to get lost so he published it here